Performance Accountability of Civil Servants at the Community and Village Empowerment Service Regency East Bolaang Mongondow - Redjeb, Djohar Murdiyanto; Mandagi, Marthinus; Mamonto, Fitri H. (Technium Social Sciences Journal, 2022)
The study aims to describe and analyze the Performance Accountability of Civil Servants at the Community and Village Empowerment Service Regency East Bolaang Mongondow and the Causes of Weakness in PNS Performance Accountability. The method used is qualitative method study. The results of research that researchers have obtained are namely: 1) Still available the leader who is also a civil servant has not known by specific function and form a must service given to the community; 2) some employees are still slow and less responsive in complete Duty work, and yet know and understand by particular procedure or SOP used in doing tupoksi; 3) Still available less staff responsive when accepting tasks assigned by leaders or service, even performance shown by employees still not yet entirely under the rules that the government has determined; 4) Coordination Among leaders and employees already walk with pleasing, but not acceptable there is an appreciation by Theory or materials provided to employees who have doing Duty with good; 5) Still available one until two leaders who show attitude ignorance to employees who have violated rules. Factors that cause weak Accountability of PNS Performance at the Community and Village Empowerment Service Regency East Bolaang Mongondow, namely: 1) Lack of knowledge of civil servants in the service about the rules, especially the latest rules related to the performance of civil servants; 2) Lack incentives provided for employees; 3) Still lacking understanding of employees related Duty principal and function; 4) Some employees in the office still anything yet discipline related time work; 5) some employees do not work on the completed task given, and more choose interest personal than rice interest organization.